PROFESIONALITAS GURU DAN PEMBELAJARAN KONTEKSTUAL - Salikin, Hairus (Jurnal Pengembangan Pendidikan, 2011)
Abstract. This concise paper elaborates a certainconsideration relacted toa a current situation of education in Indonesia. Thequality of education in our country is relatively low compared to that of othercountries like Malaysia, Singapore, and Australia. Teachers and lectures areencouraged to be professional when doing learning and teaching process. This isbecause; teachers and lecturers are of extremely important in that process.Even, if a very high technology is applied, the learning and teaching processwill never be meaningful without them. Professional teachers/lecturers musthave three things simultaneously: expertise, commitment, and skill. Besides,contextual teaching and learning (CTL) must be carried out to make students seemeaning in the academic material they are studying by connecting the subjectswith their daily lives. By doing so, it is expected that the learning andteaching process could be better. Finally professional teachers and CTL are twothings which cannot be separated when the academic atmosphere is very muchconcerned. Key words : teachers/lecturers, professional, CTL